Accidental Intravenous Administration of Simethicone in a 4-Year-Old Patient: A Case Report - Agnė Lozovskytė; Gabija Laubner Sakalauskienė; Robertas Badaras (Acta Medica Lituanica)
Simethicone is an antiflatulent medication exclusively administered orally, thus its systemic effects remain unknown. We present a case of an inadvertent intravenous administration of simethicone to a 4-year-old patient, precipitating respiratory difficulty, cyanosis, and altered mental status. The patient’s condition improved rapidly with appropriate interventions, leading to discharge in a fully recovered state. To date, only one documented instance of intravenous simethicone administration exists in medical literature.